Early Risk Factors and Developmental Pathways to Chronic High Inhibition and Social Anxiety Disorder in Adolescence - Essex, Marilyn J. (2009)
OBJECTIVE: Evidence suggests that chronic high levels of behavioral inhibition are a precursor of social anxiety disorder (SAD). This study identified the early risk factors for and developmental pathways to chronic high inhibition among school-age children and its association with SAD by adolescence. METHOD: A community sample of 238 children was followed from birth to Grade 9. Mothers, children, and teachers reported on children's behavioral inhibition from Grades 1 to 9. Lifetime history of psychiatric disorders was available for the subset of 60 (25%) children who participated in an intensive laboratory assessment at Grade 9. Four early risk factors were assessed: female gender; exposure to maternal stress during the infancy and preschool periods and at child age 4.5 years; early manifestation of behavioral inhibition, and elevated afternoon salivary cortisol levels. RESULTS: All four risk factors predicted higher and more chronic inhibition from Grade 1 to Grade 9, and together, defined two developmental pathways. The first pathway in female children was partially mediated by early evidence of behavioral inhibition and elevated cortisol levels at age 4.5 years. The second pathway began with exposure to early maternal stress and was also partially mediated by childhood cortisol levels. By Grade 9, chronic high inhibition was associated with a lifetime history of SAD. CONCLUSIONS: Chronic high levels of behavioral inhibition are associated with SAD by adolescence. The identification of two developmental pathways suggests the potential importance of considering both sets of risk factors in developing preventive interventions for SAD.